A Facile Approach to Catalyst-Free Cyanation and Azidation of Organic Compounds and a One-Pot Preparation of 5-Substituted 1H-Tetrazoles by Using a Dimethyl Sulfoxide–Nitric Acid Combination - Nasseri, Mohammad Ali; Alavi, Seyyedeh Ameneh; Mahmoudi, Boshra; Kazemnejadi, Milad (Synlett, 2019)
In this study, cyanations or azidations of imines were performed by using hydroxy(dimethyl)-λ4-sulfanecarbonitrile or azido(dimethyl)-λ4-sulfanol, respectively, prepared in situ by treatment of potassium cyanide or sodium azide with a dimethyl sulfoxide–nitric acid combination. Furthermore, a one-pot preparation of 5-substituted 1H-tetrazole derivatives was carried out by using this reagent combination in the presence of an aldehyde, hydroxylamine hydrochloride, and sodium azide under mild conditions.
Keywords: dimethyl sulfoxide; nitric acid; Strecker reaction; amino nitriles; amino azides; tetrazoles